Pengaruh Self Efficacy, Kompetensi dan Pengembangan Karir Terhadap Kinerja Guru di Sekolah Menengah Pertama Negeri 3 Sidoharjo - Rizvi Aulia Dewi Utami; Asih Handayani (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the influence of self-efficacy, competence, and career development on teacher performance at SMP Negeri 3 Sidoharjo. The research background shows that all teachers (100%) have "Good" performance category, but none have achieved the "Very Good" category. Pre-research survey results identified problems in the use of less varied teaching methods (77% of teachers), limitations in developing learning media (40% of teachers), and lack of participation in continuing education (37% of teachers). The research method uses a quantitative approach with saturated sampling technique involving 30 civil servant teachers. The research instrument was a questionnaire using a 1-5 Likert scale. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS software. The results showed that: (1) Self-efficacy does not significantly influence teacher performance with path coefficient 0.211, t-statistic 0.864, and p-value 0.388 > 0.05; (2) Competence has a positive and significant effect on teacher performance with path coefficient 0.578, t-statistic 2.614, and p-value 0.009 < 0.05; (3) Career development does not significantly influence teacher performance despite having the highest path coefficient 0.436, t-statistic 1.414, and p-value 0.158 > 0.05. The R² value of 0.592 indicates that the three variables can explain 59.2% of the variance in teacher performance. This study concludes that competence is the dominant factor affecting teacher performance, while self-efficacy and career development have not yet made significant contributions. Recommendations for schools are to improve teacher competency development programs, especially in aspects of student learning outcome research capabilities and development of innovative learning media.